2010
DOI: 10.1016/j.expneurol.2010.07.020
|View full text |Cite
|
Sign up to set email alerts
|

The plasma membrane redox system is impaired by amyloid β-peptide and in the hippocampus and cerebral cortex of 3xTgAD mice

Abstract: Membrane-associated oxidative stress has been implicated in the synaptic dysfunction and neuronal degeneration that occurs in Alzheimer’s disease (AD), but the underlying mechanisms are unknown. Enzymes of the plasma membrane redox system (PMRS) provide electrons for energy metabolism and recycling of antioxidants. Here, we show that activities of several PMRS enzymes are selectively decreased in plasma membranes from the hippocampus and cerebral cortex of 3xTgAD mice, an animal model of AD. Our results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…Other reports indicate that altered NQO1 expression is related to the pathogenesis of Alzheimer°s disease (AD) [25], [26], and suggest a potential neuroprotective role for NQO1 in diseases involving metabolic and oxidative stresses including AD [27]. NQO1 can protect cultured cells against toxic insults by regulating PMRS activity [28].…”
Section: Introductionmentioning
confidence: 99%
“…Other reports indicate that altered NQO1 expression is related to the pathogenesis of Alzheimer°s disease (AD) [25], [26], and suggest a potential neuroprotective role for NQO1 in diseases involving metabolic and oxidative stresses including AD [27]. NQO1 can protect cultured cells against toxic insults by regulating PMRS activity [28].…”
Section: Introductionmentioning
confidence: 99%
“…We showed that administration of coenzyme Q10 in the diet to Tg19959 mice, which have two mutations in the AβPP gene, significantly reduced oxidative damage to proteins, the numbers of amyloid plaques, amyloid plaque burden, amyloid-β 1-42 levels, and it improved performance on the Morris water maze test [13]. A recent report showed that in addition to increased oxidative stress, levels of coenzyme Q10 were reduced in transgenic AD mice expressing both AβPP and tau mutations [41]. However, it is not known whether coenzyme Q10 can affect tau induced pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy neurons respond to the oxidative stress triggered by excitatory synaptic activity by activating the transcription factors NF-κB and Nrf2 which, in turn induce the expression of SOD2 and HO1, respectively 81,82 . Another defense against oxidative stress that is adversely impacted in aging and AD is the plasma membrane redox system, which includes the enzymes NADH-quinone oxidoreductase 1 (NQO1), NADH-ferrocyanide reductase, NADH-coenzyme Q10 reductase, and NADH-cytochrome c reductase 83, 84 .…”
Section: Compromised Adaptive Cellular Stress Responses and Ilodmentioning
confidence: 99%